Hyperimmunoglobulin E syndrome and multiple brain abscesses - Sahoo, Sushama; Ganguly, Tusti (Indian Journal of Child Health, 2014)
Hyperimmunoglobulin E (HyperIgE) syndrome is a rare primary immunodeficiency disease characterized by recurrent skin and pulmonary infections and an elevated serum IgE level. We report a female neonate with hyperIgE syndrome who presented with multiple brain abscesses and superficial cold abscesses caused by Staphylococcus aureus and also developed pneumonia later on. On follow-up, she developed pneumonia twice and cold abscess once. She responded well to conservative management.